2014
DOI: 10.15241/gb.4.5.426
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of School Factors on School Counselor Burnout: A Mixed-Methods Study

Abstract: School counselors are a well-positioned resource to reach the significant number of children and adolescents with mental health problems. In this special school counseling issue of The Professional Counselor, some articles focus on systemic, top-down advocacy efforts as the point of intervention for addressing child and adolescent mental health. Other articles investigate improving child and adolescent mental health through a localized, groundlevel approach by developing school counselors' competency areas and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
103
3
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 29 publications
7
103
3
5
Order By: Relevance
“…Therefore, this research examined these relationships as a means to understand the complex factors associated with school counselor burnout and stress. It was suggested that school counselors might be struggling with feelings of burnout and a decrease in job satisfaction (Bardhoshi et al, ; Harnois, ; Mathews, ) related to their changing roles and job responsibilities. Although burnout and stress are not diagnosable concerns, stress can exacerbate or trigger more serious mental illness (Jason, Fennell, & Taylor, ), so seeking support is important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this research examined these relationships as a means to understand the complex factors associated with school counselor burnout and stress. It was suggested that school counselors might be struggling with feelings of burnout and a decrease in job satisfaction (Bardhoshi et al, ; Harnois, ; Mathews, ) related to their changing roles and job responsibilities. Although burnout and stress are not diagnosable concerns, stress can exacerbate or trigger more serious mental illness (Jason, Fennell, & Taylor, ), so seeking support is important.…”
Section: Discussionmentioning
confidence: 99%
“…If school counselors believe they will seek help for a mental illness if and when it develops, perhaps they will be able to cope effectively with job stressors, thus helping themselves and providing better services to students. Researchers (Bardhoshi et al, ; Harnois, ; Mathews, ) have suggested that school counselors might be in danger of developing burnout and might struggle with satisfaction related to their changing work responsibilities, so perhaps seeking mental health support as a preventative measure will assist them with ensuring that these stressors do not become larger mental health issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because these materials are too advanced for most educated juniors and seniors, the online college and university exploration process must be linguistically difficult for illiterate parents, parents and students whose first language is not English, families surviving poverty, and first-generation college students. Considering the importance of high school counselors in the college exploration process (Corwin, Venegas, Oliverez & Colyar, 2004), their high burnout rates (Bardhoshi, Schweinle & Duncan, 2014) and overwhelming student caseloads (McDonough, 2005) renders the university website a critical source of pre-college information for aspiring college students from all backgrounds. The readability of university-authored web materials is problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dual-job holding may increase job stress and decrease quality of life (Jamal, Baba, & Rivière, 1998). Findings in a study conducted with professional school counselors who were also required to perform noncounseling duties revealed an increased level of burnout perceived by the participants, including exhaustion and deterioration of personal life (Bardhoshi, Schweinle, & Duncan, 2014). In addition, Kolodinsky, Draves, Schroder, Lindsey, and Zlatev (2009) found that paperwork and other noncounseling duties interfered with the roles of school counselors and were, indeed, a source of job stress and dissatisfaction for them.…”
mentioning
confidence: 99%